2019
DOI: 10.2174/1389201020666190215103505
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Oral Glutarimide Derivative XC8 Suppresses Sephadex-Induced Lung Inflammation in Rats and Ovalbumin-induced Acute and Chronic Asthma in Guinea Pigs

Abstract: Background: Corticosteroids are the preferred option to treat asthma, however, they possess serious side effects and are inefficient in 10% of patients. Thus, new therapeutic approaches for asthma treatment are required. Objective: To study the efficacy of a novel glutarimide derivative XC8 in a Sephadex-induced lung inflammation in rats as well as in acute and chronic ovalbumin-induced allergic asthma in guinea pigs. Method: Rats were treated with 0.18-18 mg/kg of XC8 intragastrically 4 times (24 h and 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Acid is known to activate the TRPV1 and TRPA1 channels, but the activation of the airway sensory nerve depends on the magnitude and rate of pH change [ 14 ]. Before we found that the most pronounced anti-asthmatic effect of XC8 on guinea pigs was observed in the dose range of 1.4–7.0 mg/ kg, which corresponds to 20–100 mg per day for humans [ 33 ]. In phase 2a clinical trial, the highest anti-asthmatic effect of XC8 was observed for a dose of 100 mg per day [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acid is known to activate the TRPV1 and TRPA1 channels, but the activation of the airway sensory nerve depends on the magnitude and rate of pH change [ 14 ]. Before we found that the most pronounced anti-asthmatic effect of XC8 on guinea pigs was observed in the dose range of 1.4–7.0 mg/ kg, which corresponds to 20–100 mg per day for humans [ 33 ]. In phase 2a clinical trial, the highest anti-asthmatic effect of XC8 was observed for a dose of 100 mg per day [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The small molecule drug XC8 (glutarimide derivative) developed by Pharmenterprises LLC was shown to affect the influx of eosinophils into bronchoalveolar lavage (BAL) in a model of lung inflammation or asthma in rats and guinea pigs [ 33 ]. We demonstrated the complete safety of XC8 in healthy probands in phase 1 clinical trial [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Subjects underwent a screening period of up to 14 days, during which their eligibility was assessed. Thirty-two healthy subjects were allocated to 3 dosing groups (10,50, and 200 mg dosing) and randomized to treatment with XC8 or placebo in a 3:1 ratio (6 subjects receiving 10 and 50 mg XC8 and 2 placebo in treatment groups 1 and 2 and, and 12 subjects receiving 200 mg XC8 and 4 placebo in treatment group 3). Due to the dose escalating design (see 2.2 Study conduct) investigators and subjects were double-blinded regarding the randomization to active treatment and placebo, but not to the dosing group.…”
Section: Methodsmentioning
confidence: 99%
“…XC8 (histamine glutarimide) is a novel anti-asthmatic agent which targets eosinophilic migration and mast cell degranulation by inhibition of maturation of chemokines (CCL2, CCL7, CCL8, CCL13). A previous study has shown that XC8 reduces airway resistance and eosinophil counts in bronchoalveolar lavage and lung tissue in sephadex induced lung inflammation in rats and ovalbumin induced asthma in guinea pigs [10].…”
Section: Introductionmentioning
confidence: 91%
“…We have shown earlier that the derivatives of biogenic amines (peptidoamines) are effective against some inflammatory diseases [20][21][22]. We have found that the glutarimide derivative XC8 reduces the influx of eosinophils into bronchoalveolar lavage (BAL) in a Sephadex-induced lung inflammation model in rats [23]. In a model of acute and chronic asthma, XC8 significantly reduced the number of eosinophils in BAL, degranulating mast cell and goblet cell number in the lung tissue and specific airway resistance.…”
Section: Introductionmentioning
confidence: 99%